2010
DOI: 10.1016/j.bpj.2009.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal Interactions Are Responsible for Tertiary Structure Formation in Staphylococcal Nuclease

Abstract: Rapid molecular collapse mediated by nonlocal interactions is believed to be a crucial event for protein folding. To investigate the role of nonlocal interactions in tertiary structure formation, we performed a nonlocal interaction substitution mutation analysis on staphylococcal nuclease (SNase). Y54 and I139 of wild-type (WT) SNase and Delta140-149 were substituted by cysteine to form intramolecular disulfide bonds, respectively called WT-SS and Delta140-149-SS. Under physiological conditions, the reduced fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Beyond such observations, by focusing on the pressure unfolding reaction proper, we have characterized, with unprecedented structural and energetic resolution, the pressure unfolding landscape of SNase and its variants. Deletion mutagenesis (33), H/D exchange (34,35), and mechanical unfolding experiments (36) all at atmospheric pressure have provided a consistent picture of the modular nature of SNase with two subdomains, an N-terminal β-barrel core domain that includes helix 1, and a C-terminal domain consisting primarily of helix 3, with helix 2 acting as an interface between the two subdomains and the C-terminal loop Leu-137 to Ser-141 locking the protein into its correct tertiary structure through long range contacts (37,38). Besides the typical cis/trans proline isomerization observed within the unfolded states on a slow time scale, multiphasic kinetics have been detected in a stopped-flow study of a proline-free variant of SNase (39), suggesting the accumulation of on-pathway intermediate states.…”
Section: Discussionmentioning
confidence: 97%
“…Beyond such observations, by focusing on the pressure unfolding reaction proper, we have characterized, with unprecedented structural and energetic resolution, the pressure unfolding landscape of SNase and its variants. Deletion mutagenesis (33), H/D exchange (34,35), and mechanical unfolding experiments (36) all at atmospheric pressure have provided a consistent picture of the modular nature of SNase with two subdomains, an N-terminal β-barrel core domain that includes helix 1, and a C-terminal domain consisting primarily of helix 3, with helix 2 acting as an interface between the two subdomains and the C-terminal loop Leu-137 to Ser-141 locking the protein into its correct tertiary structure through long range contacts (37,38). Besides the typical cis/trans proline isomerization observed within the unfolded states on a slow time scale, multiphasic kinetics have been detected in a stopped-flow study of a proline-free variant of SNase (39), suggesting the accumulation of on-pathway intermediate states.…”
Section: Discussionmentioning
confidence: 97%
“…These early folding events enforce constraints that drastically reduce the conformational space available to the ensemble of protein molecules, which in turn create bias toward the native structure. 6,35,36 This is a typical cross-linking effect.…”
Section: The Dimensions Of the 5-ms Transient Collapsed Ensemblementioning
confidence: 97%
“…100 and 300 μs). Kato et al (2010) studied the folding of mutants of S. nuclease, where NLIs were perturbed and concluded that the native NLIs established at the early stage of the folding process facilitate further secondary structure formation. Meisner and Sosnick (2004) studied the kinetics of folding of a two-chain engineered protein in which helicity and collision rate can be varied and concluded that an unstructured encounter complex can successfully initiate rapid folding, with helix formation occurring at a later stage.…”
Section: Direct and Indirect Findings Consistent With The Closed Longmentioning
confidence: 99%